Weaponizing Memory: The Legal Implications of Russia’s Monument Policy on Occupied Territories of Ukraine - Vorobiova, Anastasiia (PRAWO i WIĘŹ, 2025)
This article explores Russia’s use of monuments as tools of ideological control in occupied Ukrainian territories following the 2022 invasion. Focusing on the removal, alteration, or erection of monuments and the reconfiguration of symbolic space, the study situates these actions within the frameworks of international humanitarian law and international human rights law. The article argues that by dismantling Ukrainian memorials and restoring Soviet symbols, Russia seeks to rewrite historical memory and impose its narrative, thus violating the conservationist principle of occupation and undermining cultural rights. Drawing on the concepts of memoricide and identicide, it calls for stronger legal safeguards to protect national memory and cultural identity under occupation in contemporary armed conflicts.